Judgment in managerial decision making - Bazerman, Max H. (John Wiley & Sons, 1998)
Decision making plays a crucial role in managerial life. But too often, our decisions are clouded by personal biases and uncertainty. This brief book shows readers how to identify their own biases in order to make better decisions. Experimental in approach, the book teaches decision making by involving the reader in decision quizzes.